THE DOSE DISTRIBUTION FROM IRIDIUM-192 SOURCE ON INHOMOGENEOUS PHANTOM BY MONTE CARLO SIMULATION - Penta Krisna, Fitria
Radiation sources in brachytherapy are placed near or within the target. Therefore, it requires the optimum dose distribution to decrease the dose at the organ risk. The human body is composed of many different densities of tissue. However, in a clinical calculation, the human body is assumed as homogeneous. This study aims to analyze the dose distribution of Ir-192 at different source locations and inhomogeneous mediums using Monte Carlo simulations. The DOSXYZnrc program was used to obtain the dose distributions by applying several parameters. The parameters were; (a) a water phantom of volume 10x10x10 cm3 of density 1 g/cm3, (b) an inhomogeneous phantom of volume 4x4x4 cm3 of density 1.04 g/cm3. (c) The voxel of volume 0.2x0.2x0.2 cm3. (d) The simulation parameters ECUT 0.521 MeV, PCUT 0.01 MeV, and 1x108 the number of particles. Nine of Ir-192 line sources distributed at certain coordinates with three distance variation models, namely Model A, Model B, and Model C, with each distance between sources 0.5 cm, 1.0 cm, and 1.5. The obtained results were dose profiles, isodose curves, and ????-index. Dose profiles resulted from DOSXYZnrc showed the penumbra width of 80-20% for each distance variation of 0.61 cm model A, 0.66 cm model B, 0.84 cm model C and width of the percent difference of FWHM for the three of them was 3%. The isodose curves and ????-index, which were analyzed using MATLAB program, showed that the average value of ????-index was outside the tolerance zone, which was ?1 for the three variations of distance. It caused the obtained GPR to have a value of less than 95% for criteria of 3 mm and 3%. The conclusion of this research was the existence of an inhomogeneous medium, and the variation of source position was able to cause the change of dose distribution